Partisipasi Masyarakat Dalam Pembangunan Kampung - Andri Irawan; Edy Sunandar (Universitas Islam Darul Ulum Lamongan, 2020)
Community participation is a component that plays a very important role in implementing development in the village, because community involvement will have an impact on the benefits of development results for the village community, starting from planning, implementing, and utilizing the results of development in the village. The results showed that the coverage indicators were not implemented properly. Village development programs were only discussed by a few elements and did not involve all elements of society. Then there is still minimal space given by the village government to the community. In addition, the livelihoods of local people who require going to fields and forests make it difficult for the village government to empower them so that indicators of empowerment are still not visible there. Obstacles to participation in the community related to the development of Kampung Kamangi include the lack of public awareness of the importance of being involved in any development in the village, and the lack of space provided by the village government to the people who will participate.